2013
DOI: 10.1002/jhbp.9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two editions of Tokyo guidelines for the management of acute cholangitis

Abstract: Two guidelines are reproducible and reliable in AC diagnosis but different in severity grading. TG13 are more practical for immediate severity grading, enabling planning treatment upon admission. Intrahepatic obstruction is a new candidate predictor of 30-day mortality for further assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 20 publications
1
44
0
2
Order By: Relevance
“…Fifteen of the 16 articles reviewed were retrospective cohort studies reviewing clinical records. Two of these 15 articles retrospectively assessed data from a prospectively generated database intended for use in research . The only prospective study identified in this search was by Csendes et al ., where participants having surgery for common bile duct (CBD) stones were divided into those with and without AC based on aspirated fluid from the CBD …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen of the 16 articles reviewed were retrospective cohort studies reviewing clinical records. Two of these 15 articles retrospectively assessed data from a prospectively generated database intended for use in research . The only prospective study identified in this search was by Csendes et al ., where participants having surgery for common bile duct (CBD) stones were divided into those with and without AC based on aspirated fluid from the CBD …”
Section: Resultsmentioning
confidence: 99%
“…Nine articles identified the location of participant recruitment which included three from the USA, three from Japan and one each from Chile, France, Hong Kong and China . One study recruited participants from multiple centres, all of which were in Japan .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholecystitis and Cholangitis in Tokyo did not include the APACHE II system for severity assessments of acute cholangitis because the advantages of this system were not satisfactorily validated and its disadvantages were difficult to calculate (16). Following the initial publication of the Tokyo guidelines for the management of acute cholangitis (TG 07), a new guideline with a different severity grading system was published in 2013 (TG 13) in an attempt to improve practicality and the quality of care (8). However, the severity assessment criteria, which include cardiovascular, nervous, respiratory, renal, hepatic, and hematologic dysfunction, require complex items such as baseline characteristics (age), vital signs (fever, disturbance of consciousness, and hypotension), and laboratory results (WBC, platelets, creatinine, PT-INR, hyperbilirubinemia, hypoalbuminemia, and PaO 2 /FiO 2 ) accompanied with diagnostic criteria for acute cholangitis (fever, evidence of inflammatory response, jaundice, abnormal liver function and biliary dilatation, and aetiology from imaging study findings); accordingly, this guideline was not easily applicable to an emergency setting (8).…”
Section: Discussionmentioning
confidence: 98%
“…Notably, however, severe forms of acute cholangitis can lead to life-threatening conditions such as sepsis, septic shock, multiple organ failure, and death (1,3,5,6) and despite the above-mentioned advances in therapy, the mortality rates of patients with severe acute cholangitis remain as high as 8% to 10% when postoperative and malignant biliary obstructionassociated mortality are included (3,7,8). Nowadays, the tasks of early recognition and stratification of the risks of severe infection and sepsis development remain challenging, particularly in terms of attempts to improve the clinical outcomes of patients with acute cholangitis.…”
Section: Introductionmentioning
confidence: 99%